Live-cell metabolic analyzer protocol for measuring glucose and lactate metabolic changes in human cells - Kenji Miki; Mikako Yagi; Ko Igami; Hiroki Kittaka; Akito Tani; Natsuki Horiuchi; Satoshi Fukumoto; Koji Yoshimoto; Takeshi Uchiumi (STAR Protocols)
Summary: Understanding metabolic conditions related to glycolysis dependence is crucial for developing new treatments in cancer and regenerative medicine. This protocol details a method for using the live-cell metabolic analyzer (LiCellMo) to measure continuous changes in glucose consumption and lactate production in cultured human cells. LiCellMo provides real-time data on consecutive metabolic changes, improving measurements of these processes in various contexts, including in cancer and regenerative treatments. : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.